2020
DOI: 10.30970/jps.24.1601
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of thermodynamic stability of Fe–B alloys

Abstract: Цю працю можна використовувати на умовах Мiжнародної Публiчної Лiцензiї Creative Commons 4.0 "Iз Зазначенням Авторства". Поширюючи цей матерiал, потрiбно вказувати авторiв i назву статтi, журнальне цитування та DOI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Borocementite formation can be explained by the fact that some carbon atoms in cementite were replaced by boron atoms. Filonenko [ 141 ] confirmed that boron atoms can substitute up to 80% (at.) of carbon atoms in cementite (Fe 3 С).…”
Section: Resultsmentioning
confidence: 99%
“…Borocementite formation can be explained by the fact that some carbon atoms in cementite were replaced by boron atoms. Filonenko [ 141 ] confirmed that boron atoms can substitute up to 80% (at.) of carbon atoms in cementite (Fe 3 С).…”
Section: Resultsmentioning
confidence: 99%